(untitled) (International Journal of Physiology, 2025)
Background: The bark of Combretum glutinosum Perr. (Combretaceae) is traditionally used in the treatment of arterial high blood pressure in Senegal. The aim of this study was to determine the vasorelaxant effect of a methanolic fraction of Combretum glutinosum bark extract (MSCG01) on isolated porcine coronary arteries and to investigate the underlying mechanism. Methods: Rings of porcine coronary arteries were suspended in organ chambers to record changes in isometric tension. Rings with intact endothelium were incubated in the presence or absence of various inhibitors, including L-nitro-arginine (L-NA), an inhibitor of endothelial nitric oxide synthase (eNOS), UCL, an inhibitor of calcium-dependent small conductance potassium channels (SKCa), and Tram-34, an inhibitor of calcium-dependent intermediate conductance potassium channels (IKCa). Indomethacin (INDO), an inhibitor of cyclooxygenases, was also used. Thirty minutes after incubation with an inhibitor, the rings were contracted with U46619, a thromboxane A2 mimetic, and subsequently relaxed with increasing concentrations of MSCG01. In some experiments, the endothelium was removed before contraction with U46619 and relaxation with MSCG01. Results: MSCG01 induces 100% relaxation at 10 µg/ml in endothelium-intact artery rings pre-contracted with U46619. The MSCG01-induced an endothelium-dependent relaxation mediated by nitric oxide (NO), but not by endothelium-derived hyperpolarizing factors (EDH) or prostanoids. Conclusions: Combretum glutinosum induces vasodilation which may contribute to explain its antihypertensive effect and its use in traditional African medicine.